Active Learning and Technology Approaches for Teaching Immunology to Undergraduate Students - Stranford, Sharon A.; Owen, Judith A.; Mercer, Frances; Pollock, Roberta R. (Frontiers in Public Health, 2020)
Immunology is a fascinating and extremely complex field, with natural connections to many disciplines both within STEM and beyond. Teaching an undergraduate course in immunology therefore provides both opportunities and challenges. Significant challenges to student learning include mastering the volume of new vocabulary and figuring out how to think coherently about a physiological system that is so anatomically disseminated. More importantly, teaching immunology can be complicated because it requires students to integrate knowledge derived from prior introductory courses in a range of fields, including cell biology, biochemistry, anatomy and genetics. However, this also provides an opportunity to use the study of the immune system as a platform on which students can assemble and integrate foundational STEM knowledge, while also learning about a new and exciting field. Pedagogical theory has taught us that students learn best by engaging with complicated questions and by thinking metacognitively about how to approach solutions. Building this skill set in today’s students, who now hail from a much wider demographic and who are accustomed to acquiring their knowledge from a variety of different media, requires a new set of teaching tools. Using perspectives from four different immunology educators, we describe a range of student-centered, active learning approaches that have been field-tested in a number of different immunology classrooms and that are geared to a variety of learning styles.